Observation of binary spectral jumps in color centers in diamond - Mu, Zhao (2022)
Optical “blinking” normally refers to a switching behavior of fluorescence for quantum emissions between “ON” and “OFF” state. For quantum dots, single molecules, and nitrogen-vacancy centers in diamond, it usually stems from conversions between two different charge states, with one emitting strong and bright fluorescence while the other scattering weak or no fluorescence. Here, a different type of blinking from single emitters in ion implanted diamond is reported, with both blinking states exhibiting detectable photoluminescence under nonresonant excitation. Thanks to the low jumping rates, the dynamics of the emission can be directly monitored. The quadratic power dependence of the conversion rates suggests the possibility of two-photon ionization process in quantum jumps. This work provides extra insights into the photodynamics of the spectral jumps on defect-based single-photon emitters hosted in wide-bandgap semiconductors.